Nuclear Program of Iran and its Repercussions on the Gulf Cooperation Council (GCC) Countries - Alaslamiy, Seadi; alsyd, Dalal (Dirasat: Human and Social Sciences, 2022)
This study aims to analyze the Iranian nuclear program and its implications for the GCC countries, and in the framework of that, it was addressed three axes; the emergence and development of the Iranian nuclear program, and then the impact of it on the Gulf region, and finally the official positions and visions of the GULF Cooperation Council countries of the Iranian nuclear program. To achieve the objectives of the study, the historical approach has been used in order to track the historical roots of the Iranian nuclear file, and the descriptive analytical approach to analyze information. The study reached several conclusions, the most important of which is that the period of the 1950s was the actual beginning of the adoption of the Iranian nuclear program, and that the Iranian nuclear program negatively affects the Gulf states as it threatens regional stability in the Gulf region and leads to the destabilization of the economic security of the Gulf States of the Arab Gulf, and the official positions on Iran's nuclear program were fragmented, the most important of which was the recognition and affirmation of Iran's right to preserve its nuclear technology for peaceful uses and support a peaceful and diplomatic solution to the Iranian nuclear crisis. In light of these findings, some recommendations and proposals have been reached, the most important of which is to draw the attention of Arab diplomacy to play an important role against the Iranian nuclear issue.